ITOC2 – 038. Role of exosomes in immune suppression. (March 2015) - Huber, Veronica; Vallacchi, Viviana; Di Guardo, Lorenza; Cova, Agata; Canevari, Silvana; Santinami, Mario; Bollati, Valentina; Rodolfo, Monica; Rivoltini, Licia
Abstract : Exosomes are endosome-derived nanovesicles involved in intercellular cross-talk through the transfer of proteins and genetic material. In cancer, exosomes can contribute to mould host micro- and macroenvironment, conditioning tumour immunity both at local and systemic level. We have been collecting evidence that these nanovesicles exert a broad array of detrimental effects on the immune system, ranging from apoptosis in activated antitumour T cells to impairment of monocyte differentiation into dendritic cells and induction of suppressive effectors. More recently, we observed that cells with phenotypic and functional properties overlapping with those displayed by myeloid-derived suppressor cells (MDSC) can be generated in vitro by culturing normal monocytes with exosomes released by melanoma cells (Exo-MDSC). Compared to untreated monocytes, Exo-MDSC show increased mRNA level and release of protumourigenic and immunosuppressive cyto/chemokines, down-modulate the expression of HLA-DR and TLRs, and acquire the ability to inhibit T cell proliferation. A defined gene-expression and miRNA signature, involving HIF1alfa, IL6 and several immune-related genes, has been identified in Exo-MDSC as triggered by exosomal TGFb, CCL2 and selected miRNA. Given their ability to efficiently recirculate in body fluids, tumour exosomes could spread systemically and directly condition myelopoiesis. This hypothesis is supported by the evidence that peripheral MDSC from melanoma patients share defined traits of Exo-MDSC gene-expression and miRNA signature, in addition with phenotypic and functional features of these cells. MDSC accumulate in peripheral blood of melanoma patients as an early event and in association with disease progression. High MDSC frequency is an acknowledged negative prognostic factor in several tumour histologies and predicts poor response to immunotherapy, including checkpoint blockade. The identification of exosomes as a potential pathway responsible for MDSC mobilisation and accrual paves the way to the development of novel immune-based therapeutic strategies and prognostic biomarkers in cancer patients. Supported by Italian Association For Cancer Research – AIRC Grant code 12162.